Treatment Strategy for Irreparable Rotator Cuff Tears - Oh, Joo Han; Park, Min Suk; Rhee, Sung Min (Clinics in orthopedic surgery, 2018)
Recently, patients with shoulder pain have increased rapidly. Of all shoulder disorders, rotator cuff tears (RCTs) are most prevalent in the middle-aged and older adults, which is the primary reason for shoulder surgery in the population. Some authors have reported that up to 30% of total RCTs can be classified as irreparable due to the massive tear size and severe muscle atrophy. In this review article, we provide an overview of treatment methods for irreparable massive RCTs and discuss proper surgical strategies for RCTs that require operative management.